Cypress aphid devastation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Kenyan landscape is undergoing a dramatic change. The Mexican cypress tree Cupressus Iusitanica, which is grown on 45% of the country's total industrial forest plantation area, is falling victim to the cypress aphid, Cinara cupressi, an insect...